Magistrature and Press Media - Sánchez-Palacios Paiva, Manuel (2008)
Starting off of the freedom concept the press freedom is elaborated, it is been displayed a brief of it, from the most remote times to the most recent, as much in the world-wide scope as in the Peruvian. Reference to the limits of the press freedom is proposed by Jacques Bourquin as well as to the mission that the press must fulfill. After it, the subject is the press and the Peruvian Judicial Power, settling down that a free press and an independent Judicial Power are pillars that sustain the democracy, then makes reference to two cases that have been treated widely by the press in Peru. Finally, concludes emphasizing the pre-eminence of the liberties of expression and informalion against any right.